Imaging of multi-color fluorescence emission from leaf tissues - Benediktyová, Zuzana; Nedbal, Ladislav (Photosynthesis research, 2009)
Multi-color fluorescence emission from leaf tissues is presented as a powerful reporter on plant biochemistry and physiology that can be applied both at macro- and micro-scales. The blue-green fluorescence emission is typically excited by ultraviolet (UV) excitation. However, this approach cannot be applied in investigating intact leaf interior because the UV photons are largely absorbed in the epidermis of the leaf surface. This methodological barrier is eliminated by replacing the UV photon excitation by excitation with two infra-red photons of the same total energy. We demonstrate this approach by using two-photon excitation for microscopy of Arabidopsis thaliana leaves infected by pathogenic bacterium Pseudomonas syringae. The leaf structures are visualized by red chlorophyll fluorescence emission reconstructed in 3-D images while the bacteria are detected by the green emission of engineered fluorescence protein.
Keywords: Plant Diseases; Imaging, Three-Dimensional; Spectrometry, Fluorescence; Plant Leaves; tabák; mezofylové buňky; chlorofyl; fluorescenční spektrometrie; Nicotiana; listy rostlin; zobrazování trojrozměrné; Mesophyll Cells; Pseudomonas syringae; Arabidopsis; nemoci rostlin; Chlorophyll